Resolution of Mild Ganciclovir-Resistant Cytomegalovirus Disease with Reduced-Dose Cidofovir and CMV-Hyperimmune Globulin - Samir J. Patel; Samantha A. Kuten; Richard J. Knight; Dana M. Hong; A. Osama Gaber (Journal of Transplantation)
Ganciclovir-resistant cytomegalovirus (CMV) is associated with significant morbidity in solid organ transplant recipients. Management of ganciclovir-resistant CMV may be complicated by nephrotoxicity which is commonly observed with recommended therapies and/or rejection induced by “indirect” viral effects or reduction of immunosuppression. Herein, we report a series of four high serologic risk (donor CMV positive/recipient CMV negative) kidney transplant patients diagnosed with ganciclovir-resistant CMV disease. All patients initially developed “breakthrough” viremia while still receiving valganciclovir prophylaxis after transplant and were later confirmed to exhibit UL97 mutations after failing to eradicate virus on adequate dosages of valganciclovir. The patients were subsequently and successfully treated with reduced-dose (1-2 mg/kg) cidofovir and CMV-hyperimmune globulin, given in 2-week intervals. In addition, all patients exhibited stable renal function after completion of therapy, and none experienced acute rejection. The combination of reduced-dose cidofovir and CMV-hyperimmune globulin appeared to be a safe and effective regimen in patients with mild disease due to ganciclovir-resistant CMV.